GOVERNANCE AND ACCOUNTABILITY ISSUES IN THE DISTRIBUTION OF THE PROPERTIES OF A DECEASED PERSON: THE CASE OF NIGERIA (Journal of the Management Sciences, 2025)
The paper examined governance and accountability issues relating to the distribution of the properties of a dead person in Nigeria. This study becomes necessary as many families of deceased persons are: always at loggerheads with themselves as a result of the properties left behind by the deceased person; the huge compensations paid to executors of estates; cosmetic accountability and lack of transparency by the executors of the estate of deceased persons. The specific aim of this study was to investigate the reasons why there are continued family squabbles over the distribution of the properties of their deceased bread winner. To pursue this study, agency theory was used to guide the researcher as the executor (agent) acts on behalf of the testator (principal) after his death. The methods used to gather data were by interviewing lawyers, accountants and executors who are involved in the distribution of a dead man’s properties. The relations of deceased persons were also interviewed. Data were also gathered from books, newspapers and Journal articles. Results showed that the absence of transparency and accountability in the distribution of legacies by executors fueled the embers of bitterness and squabbles. Another result is the refusal of the executor to give legacy to whom it should be given to. Furthermore, non-equitable distribution of legacies to the beneficiaries and finally, the testators’ refusal to give gifts to some of their children. It was recommended that the testator should engage executors that are professionally qualified and having integrity; British ways of making will should stop thus giving ways to our customs and traditions. legacies should be properly and professionally written by a lawyer; the executor should honestly distribute the legacies without bias. Legacy should not be short changed by the executors by not giving a good property to whom it is due.
Keywords: Governance; Accountability; Distribution; Properties; Deceased Person; Nigeria